2021
DOI: 10.3389/fonc.2021.635774
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pyroptosis: A Promising Strategy for Cancer Treatment

Abstract: Pyroptosis, a lytic pro-inflammatory type of programmed cell death, has been widely studied in diverse inflammatory disease models. Membrane perforation and cell swelling induced by cleaved gasdermin family members is the main characteristic of pyroptosis. Emerging evidence has revealed a complicated relationship between pyroptosis and cancer. On the one hand, as inflammatory cell death, pyroptosis provides a comfortable environment for tumor proliferation. On the other hand, excessive activation of pyroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 113 publications
1
69
0
Order By: Relevance
“…Recently, several studies found that the pyroptosis signal might play a dual role in tumor development and drug response (33). On one hand, long time exposure to inflammation could facilitate tumorigenesis; on the other hand, pyroptosis could inhibit the development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies found that the pyroptosis signal might play a dual role in tumor development and drug response (33). On one hand, long time exposure to inflammation could facilitate tumorigenesis; on the other hand, pyroptosis could inhibit the development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is associated with many diseases ( Al Mamun et al, 2020 ; Al Mamun et al, 2021 ; Chu et al, 2016 ; Wang et al, 2018 ). Meanwhile, pyroptosis may mediate cell death by Caspase-1–dependent, Caspase-4/5/11–dependent, and Caspase-3/8–dependent inflammasome signaling pathways ( Antonopoulos et al, 2015 ; Yu et al, 2019 ; Chen et al, 2020 ; Liu et al, 2021 ; L.; Wang et al, 2021 ). Recently, increasing studies show that pyroptosis is associated with the development of cancer ( Al Mamun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a novel approach to immunotherapy schedule may be the depletion of TFR cells or blocking their activity with anti-CTLA-4 before anti-PD-1 therapy. The effectiveness of this approach has been proven in mouse tumor models and were also associated with better survival outcomes in a large cohort of patients with melanoma [21][22][23].…”
Section: Resistance To Immunotherapy Associated With An Impaired Function Of the Immune Systemmentioning
confidence: 99%
“…The chronic inflammation activation of pyroptosis facilitates the tumor progression, while it inhibits tumor growth during acute inflammation. However, the interaction between pyroptosis and antitumor immunity still needs further research [22,23,25].…”
Section: Resistance To Immunotherapy Associated With An Impaired Function Of the Immune Systemmentioning
confidence: 99%